Unleashing rights law, meaning, and the animal rights movement - Silverstein, Helena (Law, meaning, and violence, 1996)
Unleashing Rights is a study of the animal rights movement's efforts to advance social reform through the deployment of legal language and practices. The study looks at how prevailing understandings of rights language have shaped the attempt to put forth the idea that animals have rights, and how this attempt, in turn, offers the opportunity to reconstruct the meaning of rights. The book also examines the way litigation has influenced the movement's activities and opportunities for success. Unleashing Rights is a book that illustrates the relationship between law, social movement activism, and social change. The book joins the ongoing debate within public law scholarship that is concerned with the effectiveness of legal strategies and languages. The book also speaks to those interested in the general study of social movements and in the particular study of the animal rights movement. With its cultural approach focused on rights language and the construction of meaning, the work will be of interest to the disciplines of law and political science, as well as those who study sociology, anthropology, and philosophy.